Palladium(II)-catalyzed ring expansion of 1-vinyl-1-cyclobutanols, synthesis and coupling of α-heteroatom stannyl- and silyl-reagents, and synthesis and reactions of allenyl stannanes and asymmetric synthesis of γ-hydroxy-β-amino acid derivatives - Ranslow, Peter Benjamin Douglas, author; Hegedus, Louis S., advisor; Meyers, Albert I., committee member; Elliott, C. Michael, committee member; Barisas, B. George, committee member; McNeil, Michael R., committee member (Colorado State University. Libraries, 2003)
Conditions for the palladium(ll) catalyzed, oxidative ring expansion of α-alkoxy-1-vinyl-1-cyclobutanols were developed. Using conditions found in the literature to effect this transformatio led to isomerization of the newly formed double bond into the ring, destroying the α-alkoxy chiral center. It was found that using palladium(ll) acetate as the palladium source and DDQ as the hydride receptor led to formation of the desired alkylidenecyclopentanone products in high yield. The insertion reaction of Fisher carbene complexes into group(IV) metal hydride bonds to form the corresponding of α-heteroatom group(IV) species is a well known process. The inherent non-reactivity of these α-heteroatom group(IV) species, however, has greatly limited the utility of this reaction. Use of stannatrane hydrides as the group(IV) metal hydride species could lead to the synthesis of a-heteroatom stannatrane species that would be reactive under Stifle coupling conditions. α-Hydroxy-β-amino acids are interesting structural moieties found in several natural products. By using a novel allenyl stannane reagent, similar to those studied by Marshall, it was possible to construct a propargyl amino-alcohol system that could be transformed to the desired α-hydroxy-β-amino acid derivatives in only two subsequent steps. The requisite chiral N-oxazolidinone allenyl stannane reagents were not known, and synthesis of these reagents proved not to be trivial. The condensation reactions of these chiral Noxazolidinone allenyl stannane reagents with various aldehydes proceeded in very high yield and with good selectivity, marking the first example of nitrogen-substituted allenyl stannanes in this type of reaction. The condensation reaction tolerated many, diverse aldehydes, proving this methodology is viable for the synthesis of a variety of 1,2-amino alcohol products.
Keywords: organic chemistry